Pécs gazdasági és társadalmi helyzete az Erzsébet Tudományegyetem Pécsre költözése évtizedében - Kaposi, Zoltán (Per Aspera ad Astra, 2014)
In the period of the Austro-Hungarian Dualism (1876–1918), Pécs was one of the fastest developing cities in Hungary. The two determining factors in its development were the birth of the manufacturing industry and coal-mining which offered employment for a large number of workers. As a time of major technical innovations, this period also marks the birth of some of the world-famous private enterprises in Pécs (Zsolnay, Angster, etc.). However, following the outbreak of World War I, industrial development was arrested. During the war and the three-year-occupation of the city by Serbian troops, the economic and social structures of Pécs underwent an important change. Real income dropped, the city drained its reserves and Serbian troops ransacked the city after 1918. As a result of the great losses of resources, progress after August 1921, when the Serbian troops were withdrawn, proved to be rather ambiguous. Undoubtedly, the population of the city was rapidly growing because Pécs, offering greater possibilities, attracted many people from the wider region. At the same time, the decline of industry, together with the decrease in the demand for labour, posed a serious challenge. The production capacities of many factories had to be reduced, and there began a concentration of privately run former factories and their reorganization into shareholding companies. Until the end of 1926, coal mines owned by DGT, had to turn over most of its production to pay reparations to Yugoslavia. Between 1920 and 1930, there was a severe drop in the number of enterprises which had always played a significant role in the small-scale industries of Pécs. Although in the latter half of the 1920s there were already signs of recovery in the slow stabilization of the local economy, the private sector continued to stand on shaky legs. It was an interesting change, which coincided with the practice of other towns in the country, that in the 1920s the city took over the task of the stimulatation of economy. Pécs began to play a growing part in the functioning of local infrastructure (the supply of gas, water, and electricity; education and local transport), but it is also true that, because of these unavoidable developments, it accumulated debts in the latter half of the decade (see the Speyer Loan). The slow development of the city came to a grinding halt at the time of the global economic crisis that could be felt from the end of 1929 onwards; the rapid rise of unemployment and the loss of markets meant newer problems that were difficult to manage. (Translated by Gabriella Hartvig) Fotó: Fortepan / POTE